Psychometric properties of the Persian version of Care Dependency Scale in older people nursing home residents - Gholamreza Rajabi; Masoume Namadmalan; Roya Ghasemzade; Mahshid Foroughan; Shahla Zahednejad; Ate Dijkstra (Payesh, 2015)
objective (s): Maintaining independence and attending to the bio-psychosocial needs of elderly always have been one of the main goals of caregivers and policy-makers. This study was carried out to investigate the psychometric properties of the Persian version of Care Dependency Scale (CDS) in older people nursing home residents. Methods: This study was carried out during 2011 and 2012 among a sample of 100 older people 65 years and older residing in nursing homes in Ahvaz, Iran. First, the English version of the CDS was translated into Persian language. Then, psychometric properties of the questionnaire were assessed by several tests. To examine reliability, the Cronbach’s alpha coefficient and test-retest reliability analyses were performed. Construct validity was determined using exploratory and confirmatory factor analyses and concurrent validity was carried out using the Modified Barthel Index. Results: The Exploratory and confirmatory factor analyses indicated that CDS has 2 factors including psycho-social (65.73% of the variance) and somatic (8.71% of the variance) factors. Internal consistency as assessed by the Cronbach’s alpha coefficient was 0.95, test-retest reliability was 0.99 and it showed excellent correlation with the Modified Barthel Index (r = 0.90). Conclusion: The results study indicated that the Persian version of the CDS is reliable and valid measure for assessment of care dependency and to determine care needs among older persons.